IMPROVING THE PROFESSIONAL TRAINING OF FUTURE TEACHERS - Mamatkobilova Shodiya Azamat qizi (Galaxy International Interdisciplinary Research Journal, 2022)
The article reveals important issues of formation of professional beliefs in future teachers. Also, the issues of finding solutions to the problems of formation of feelings of loyalty, the studied aspects of the scientists of the republic, the concepts of profession, professional culture and professional beliefs are widely covered.